2022
DOI: 10.4103/jmp.jmp_115_21
|View full text |Cite
|
Sign up to set email alerts
|

Embryo/Fetus Doses from 18F-Fludeoxyglucose Radiopharmaceutical in Positron Emission Tomography/ Computed Tomography

Abstract: Aim: The embryo/fetus may be accidentally exposed to ionizing radiation. The aim of this study is to calculate embryo/fetus doses in pregnant women who underwent F-18 fludeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) scan. Materials and Methods: Between June 2015 and June 2021, 15 pregnant women underwent F-18 FDG PET/CT applied to the Genetic Research Center (GETAM). The OLINDA/EXM package program was used for internal radiation dosimetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…Furthermore, we reduced the foetal dose from the LDCT scan for AC to 0.90 mGy when the foetus was included in the FOV. This is markedly lower compared with the study of Işıkçı et al [4] that observed radiation exposure from CT scans on the foetus ranging between 8.5 and 16.0 mGy. Moreover, advancements such as the use of tin filters during LDCT acquisition could dramatically reduce radiation exposure for AC by as much as 90%, as recently demonstrated by Mostafapour et al [10].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Furthermore, we reduced the foetal dose from the LDCT scan for AC to 0.90 mGy when the foetus was included in the FOV. This is markedly lower compared with the study of Işıkçı et al [4] that observed radiation exposure from CT scans on the foetus ranging between 8.5 and 16.0 mGy. Moreover, advancements such as the use of tin filters during LDCT acquisition could dramatically reduce radiation exposure for AC by as much as 90%, as recently demonstrated by Mostafapour et al [10].…”
Section: Discussioncontrasting
confidence: 62%
“…F-fluoro-deoxy-glucose ( 18 F-FDG) positron emission tomography-computed tomography (PET/CT) imaging is widely used in oncology for diagnoses, staging and treatment response evaluation [1,2]. However, in pregnant patients, the use of 18 F-FDG PET/ CT imaging can cause a dilemma because of the radiation exposure to the foetus [3,4]. Therefore, it is crucial to minimize the radiation exposure to the foetus when performing an 18 F-FDG PET/CT scan.…”
mentioning
confidence: 99%